2005
DOI: 10.1038/sj.onc.1208935
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the protein kinase B pathway by the HPV-16 E7 oncoprotein occurs through a mechanism involving interaction with PP2A

Abstract: Protein kinase B (PKB) or Akt is one of several second messenger kinases that are activated by cell attachment and growth factor signaling, and that transmit signals to the cell nucleus to inhibit apoptosis and thereby increase cell survival during proliferation. Other viral proteins target this pathway by increasing PKB/Akt phosphorylation, and this pathway has been implicated in the transformation of human keratinocytes by HPV E6 and E7, together with activated notch 1. Here, we examine how HPV E7 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
139
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 43 publications
5
139
1
5
Order By: Relevance
“…The degradation of MAGI-2 and MAGI-3 by E6 may, therefore, result in the abolishment of PTEN function resulting in the activation of Akt-mediated cell growth. In addition, HPV-16 E7 upregulates AKT activity in both Rb-dependent and -independent manner (Westbrook et al, 2002;Pim et al, 2005;Menges et al, 2006). Taken together, these results highlight the importance of interference with the PI3 kinase/Akt-mediated signalling pathway in HPV-induced tumourigenesis.…”
Section: Discussionmentioning
confidence: 71%
“…The degradation of MAGI-2 and MAGI-3 by E6 may, therefore, result in the abolishment of PTEN function resulting in the activation of Akt-mediated cell growth. In addition, HPV-16 E7 upregulates AKT activity in both Rb-dependent and -independent manner (Westbrook et al, 2002;Pim et al, 2005;Menges et al, 2006). Taken together, these results highlight the importance of interference with the PI3 kinase/Akt-mediated signalling pathway in HPV-induced tumourigenesis.…”
Section: Discussionmentioning
confidence: 71%
“…Disruption of PI3K/Akt signaling has been reported in the malignant progression caused by two well known transforming viruses, hepatitis B virus and human papilloma virus (32,37,48,52). The hepatitis B virus oncoprotein HBx and the human papilloma virus proteins E6 and E7 have been implicated in alterations of the cellular PI3K/Akt pathway (75,76). Further supporting its importance in cancer, several reports have shown that PI3K/Akt activation contributes to chemotherapeutic resistance of leukemias (15,53,77).…”
Section: Discussionmentioning
confidence: 94%
“…Elevated mTOR activity has previously been implicated in replication of adenoviruses (38). Interestingly, E7 alone also up-regulates activating phosphorylation of PKB/AKT (39,40). It will be interesting to examine the role of mTOR in the viral productive lifecycle.…”
Section: Discussionmentioning
confidence: 98%